2019
DOI: 10.1177/0030222819846721
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Chinese Employees’ Suicide Ideation: Does Meaning in Life Matter?

Abstract: Drawing on the self-determination theory and conservation of resources, our research shed light on the linkage between organizational autonomy support and suicide ideation. Specifically, this study examined whether the negative influence of autonomy support on suicide ideation is mediated via meaning in life, and if employee’s autonomy orientations constitute a boundary condition of this relationship. To test the hypothesized model, data were collected from professional employees ( N = 687) across six organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 95 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…Consistent with previous findings ( 13 , 18 , 19 ), our findings provided empirical support on the protective role of presence of MIL against SI. The findings not only demonstrate the potential clinical relevance of using PHQ-4 as a brief and direct screening tool of SI, but also inform clinical practice on refinement of SB risk assessment via a meaning-oriented approach ( 44 ). Multigroup SEM revealed significantly greater negative indirect effects of MIL on SI via PHQ-4 in the distress group than the non-distress group.…”
Section: Discussionmentioning
confidence: 73%
“…Consistent with previous findings ( 13 , 18 , 19 ), our findings provided empirical support on the protective role of presence of MIL against SI. The findings not only demonstrate the potential clinical relevance of using PHQ-4 as a brief and direct screening tool of SI, but also inform clinical practice on refinement of SB risk assessment via a meaning-oriented approach ( 44 ). Multigroup SEM revealed significantly greater negative indirect effects of MIL on SI via PHQ-4 in the distress group than the non-distress group.…”
Section: Discussionmentioning
confidence: 73%
“…In a similar study on the relationship between life satisfaction and suicide, Santos, Ulisses, Costa, Farias and Moura ( 2016), in a survey conducted in the city of Fortaleza (CE, Brazil), found that life satisfaction was correlated positively with an attraction to life and negatively with the repulsion to life and attraction to death. In short, there was a negative correlation between quality of life and its factors (physical health, socioeconomic status, good mental health, social support, meaning of life) and risk of suicide, indicating that high levels of QoL are associated with low risk indices of suicidal ideation (Alves et al, 2016;Bamonti, Lombardi, Duberstein, King, & Orden, 2016;Melo, Sampaio, Souza, & Pinto, 2015;Costanza, Prelati, & Pompili, 2019;Oliveira et al ., 2018;Wilchek-Aviad & Malka, 2016;Liu, Usman, Zhang, Raza, & Gul, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research examining the role of such defenses following death awareness has consistently demonstrated that adhering to one’s cultural values and high self-esteem reduce the deleterious effects of such awareness and contribute to maintaining meaning in life and psychological well-being (see review by Juhl, 2019). Moreover, self-esteem and meaning in life have been associated with various attitudes toward death, such as suicidal ideation, among young adults (Lin, 2000) and professional employees (Liu et al, 2021). However, most TMT-related research has been conducted using experimental designs, and relatively little is known regarding the functionality of TMT defenses outside the laboratory.…”
Section: Introductionmentioning
confidence: 99%